Service-Oriented Synthesis of Distributed and Concurrent Protocol Specifications. (14th September 2008) - Al Dallal, Jehad; Saleh, Kassem
Abstract : Several methods have been proposed for synthesizing computer communication protocol specifications from service specifications. Some protocol synthesis methods based on the finite state machine (FSM) model assume that primitives in the service specifications cannot be executed simultaneously. Others either handle only controlled primitive concurrency or have tight restrictions on the applicable FSM topologies. As a result, these synthesis methods are not applicable to an interesting variety of inherently concurrent applications, such as the Internet and mobile communication systems. This paper proposes a concurrent-based protocol synthesis method that eliminates the restrictions imposed by the earlier methods. The proposed method uses a synthesis method to obtain a sequential protocol specification (P-SPEC) from a given service specification (S-SPEC). The resulting P-SPEC is then remodeled to consider the concurrency behavior specified in the S-SPEC, while guaranteeing that P-SPEC provides the specified service.